TANTANGAN GURU DI ERA KEKINIAN - Husnani, Husnani; Zaibi, Zaibi; Rollies, Beni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is descriptive-qualitative research, with the aim to provide an explanation of the challenges of teachers in conducting learning in the era of globalization or coolly called the contemporary era. One of them is in the use of technology to support classroom learning. The teacher also faces various other problems in various fields. The technique of collecting data is document observation. The conclusion of the study is that contemporary teachers face various challenges in the socio-cultural, political and technological fields. All of these challenges, demand the teacher, as the spearhead of learning to develop further by trying to improve their abilities.